The fundamental context of SEL for early childhood student teachers in private higher education institutions - Promsatien, Yupawadee; Kuroda, Ariyabhorn; Aerarunchot, Suwadee; Pinagalang, Sungwean (Institute of Advanced Engineering and Science, 2025)
This research examined the learning needs and the current social and emotional conditions of early childhood student teachers in private higher education institutions. The sample group responding to the questionnaire comprised 343 undergraduate students majoring in early childhood education. The target group for interviews included nine participants, which consisted of 3 deans, 3 department heads, and 3 lecturers. The research instruments consisted of a questionnaire on the state and needs of social and emotional learning (SEL) and an interview guide on the current social and emotional conditions of early childhood student teachers. The data were analyzed using percentage, mean, standard deviation, and content analysis. The findings revealed that the state of learning among pre-service teachers was at a low level, while their learning needs were high. Furthermore, the current conditions indicated that pre-service teachers require enhanced SEL opportunities. Activities fostering such learning should be designed, including group work, experiential learning, listening to others, and engaging in discussions.